Parameters Optimization of Tuned Mass Damper Using Fast Multi Swarm Optimization - Frans, Richard (Jurnal Teknik Sipil, 2019)
Tuned mass damper (TMD) has been used for vibration controller of building, especially for high rise building. TMD is one of passive device for reducing response of the structure which subjected to dynamic external disturbance such as wind, or earthquake load. TMD used its weight for reducing the vibration, TMD’s frequency has been set with structure’s frequency so that the frequency can resonate each other for reducing the response of the structure during the dynamic load. Therefore, three variables have significant effect for TMD performance which are mass ratio of TMD (m), frequency ratio of TMD (a), and damping ratio of TMD (z) which lead to two important variables of TMD properties which are stiffness and damping of TMD. This paper developed an empirical equation for obtaining the optimum parameters of tuned mass damper based on H2 norm control system and fast multi swarm optimization (FMSO). The objective function was to minimize the acceleration and displacement response of the structure. Accelerogram of El-Centro 1940 NS was chosen to be ground motion acceleration for simulating the response of the structure with and without TMD. The result shows a strong correlation both mass ratio of TMD to frequency ratio of TMD and mass ratio of TMD to damping ratio of TMD.